Adoption factors in Business-to-Consumer (B2C) e-commerce for SME in Sudan - Musbah, Abdelaziz Ahmed Mustafa (Kulliyyah of Information and Communication Technologys, International Islamic University Malaysia, 2018)
Recently, the Internet has performed and is continuously performing a major role in people's lives. A very important roles played by the Internet is in the aspect of e-commerce. In a bid to meet up with the effects of an environment that is undergoing changes, a lot of researchers stated that e-commerce offers a feasible solution to business owners and entrepreneurs. However, the few available studies concerned with Enterprises in developing countries shown evidence of delays and failure in adoption. Irrespective of the increase in the numbers of people using the Internet in Sudan, the adoption of Business-to-Consumer (B2C) by organisations is still in its early stages. The two main reasons which have provided a good motivation to the researcher to perform this study to analyze the factors that influence a decision to adopt Business-to-Consumer (B2C) are the belief on the role online shopping plays in an economy and in the lives of people in particular, as well as the limited studies which were performed. Subsequently, it employed a sequential, exploratory and mixed method, where both qualitative and quantitative approaches were combined to meet the research objectives. In the first stage, semi-structured interviews with 7 SMEs owner-managers were conducted in Khartoum, the capital city of Sudan. In the second stage, a survey involving 151 SMEs in Khartoum was conducted to examine empirically the research question. The main findings of the present study comprise of some key factors that has a significant effect on e-commerce (B2C) adoption, such as lack of good e-commerce legislation and the poor online payment system in Sudan. The study found that non-technical barriers in Sudan, which include lack of marketing plan and IT knowledge, have negatively affected people's decisions to use the technology or adopt technological initiatives. The research findings show that environmental factors in Sudan have a significant effect in adopting B2C e-commerce if compared to factors that has to do with the growth in technology and organization. The most dominant issues were unfavorable conditions due to the current economic and political status of the country, unreliable network infrastructure, and the weak power distribution in Sudan. Despite the fact they cannot fully utilise B2C e-commerce services, organisations appreciates the possible benefits offered by this technology. Consequently, findings based on research states that organisations are willing to use B2C e-commerce to enjoy benefits such as security, cost reduction, and convenience. The key motivation for adopters is the need for innovation and external competition. Both organizations and supporting organizations aim to draw immense benefits from this study in their efforts to boost B2C e-commerce adoption technology, particularly countries such as Sudan as a result of its unique economic condition.